Opozycja kultury i natury a problem historyczności nauki - Tuchańska, Barbara (Filozofia Nauki, 1998)
In the article the ideas of Joseph Margolis, concerning the relation between the problem of historicity of science and the distiction of social and natural science are discussed. Margolis rejects the nomological model of the history of science. His radical realism claims, that «historical stories» represent (in the realistic sense) that, what happens in our world. Two notions of «bering real» are introduced. The author discusses some problem, connected with Margolis’ model, concluding, that it is founded on the assumption, that scientific knowledge has to be considered as a linguistic (therefore intentional) activity, and considered in a historical context.